Nanoparticles Partially Restore Bacterial Susceptibility to Antibiotics; Materials; Vol. 17, iss. 7 - Bogdanchikova N. Nina; Vazquez-Gomez R. L. Roberto Luna; Nefedova E. V. Ekaterina Vladimirovna; Garibo D. Diana; Pestryakov A. N. Aleksey Nikolaevich; Plotnikov E. V. Evgeny Vladimirovich; Shkil N. N. Nikolay (2024, 2024)
Title screen